2020
DOI: 10.3390/ijerph17238802
|View full text |Cite
|
Sign up to set email alerts
|

Female Fertility and Environmental Pollution

Abstract: A realistic picture of our world shows that it is heavily polluted everywhere. Coastal regions and oceans are polluted by farm fertilizer, manure runoff, sewage and industrial discharges, and large isles of waste plastic are floating around, impacting sea life. Terrestrial ecosystems are contaminated by heavy metals and organic chemicals that can be taken up by and accumulate in crop plants, and water tables are heavily contaminated by untreated industrial discharges. As deadly particulates can drift far, poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 138 publications
(151 reference statements)
0
33
0
1
Order By: Relevance
“…EDCs can be released in the environment in many forms. These include pesticides, industrial waste, packaging, synthetic food and cosmetics [ 2 ]. Over the last decades, mounting scientific evidence has shown that the reproductive health of humans and wildlife has been adversely affected by the EDCs [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…EDCs can be released in the environment in many forms. These include pesticides, industrial waste, packaging, synthetic food and cosmetics [ 2 ]. Over the last decades, mounting scientific evidence has shown that the reproductive health of humans and wildlife has been adversely affected by the EDCs [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One emerging group of contaminants, endocrine-disrupting chemicals (EDCs), is exogenous substances or mixtures that cause dysfunction of the endocrine system, inducing multiple adverse health effects in humans through interaction with hormone receptors ( Schug et al, 2016 ). EDCs can be released into the environment in various forms, including pesticides, plastic debris, retardants, industrial waste, and cosmetics ( Chen et al, 2019 ; Canipari et al, 2020 ), and they can be absorbed, accumulated, and even converted to more toxic metabolites by the body ( Yuan et al, 2015 ; Ding et al, 2020 ). Studies have demonstrated that EDCs affect the reproductive systems of both sexes, causing congenital abnormalities and infertility ( Huang and Zeng, 2021 ; Walker et al, 2021 ; You and Song, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these chemicals, including BPA, TBBPA and heavy metals, may act as endocrine disruptors. Therefore, their exposure above certain thresholds during foetal or early life may cause long-lasting negative effects on growth, development and health [34][35][36][37]. In this study, we elucidated whether there are potential associations between the maternal diet, the content of some major elements, trace metals, BPA and TBBPA, as well as the FAs, microbial, and immunological profiles of human milk.…”
Section: Discussionmentioning
confidence: 99%
“…The mean (95% CI) age of the participants (n = 53) was 35 (34,36) years, ranging from 25 to 43 years (Table 1). The median (IQR) body mass index (BMI) was 24.5 kg/m 2 (20.89-27.19 kg/m 2 ).…”
Section: Demographic Characteristicsmentioning
confidence: 99%